Application of Pharmaceutical Wastewater in Planting French Marigold. Issue 3 (April 2020) - Wang, Yu; Huang, Zhidong
Abstract: Based on biological method, the harmless treatment of pharmaceutical wastewater is achieved, which is applied to planting French marigold after suitable dilution. The protein content, vitamin c content and reducing sugar content of French marigold are determined with ultraviolet absorption method. The experiment results show that planting French marigold with pharmaceutical wastewater had no bad effect on French marigold, which facilitates reutilization of pharmaceutical wastewater.